Determination of Anatolian Plate’s tectonic block boundaries with clustering analysis using GNSS sites velocities - Şeyma Şafak Yaşar; İbrahim Tiryakioğlu; Bahadır Aktuğ; Hediye Erdoğan; Çağlar Özkaymak (Geomatics, Natural Hazards & Risk)
The Anatolian Plate is an important tectonic structure containing different types of faults. In this study, block boundary studies were performed by clustering analysis using horizontal velocity data for 841 GNSS sites located on the Anatolian Plate. Four algorithms were used to determine the most appropriate cluster number. Cluster analysis was performed with K-means analysis. Different to other studies, the analysis included the location parameter for the GNSS sites in the cluster analysis. Generally block boundaries followed active fault zones and surface ruptures forming as a result of earthquakes. In this block study, 3 previously undocumented block boundaries were defined based on GNSS data. When all parameters are assessed in cluster analysis, the most appropriate cluster number was determined to be 9.